2016
DOI: 10.12965/jer.1632666.333
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial lipoprotein profile in two modes of high-intensity intermittent exercise

Abstract: The aim of present study was to compare blood lipid postprandial profile response in two modes of high-intensity intermittent exercise. Twelve individuals (6 men and 6 women) were submitted to a maximal incremental test (to determine maximal aerobic power [MAP] and V. O2peak [peak oxygen uptake]), high-intensity intermittent all-out exercise (60×8-sec bouts interspersed by 12-sec passive recovery) and fixed high-intensity intermittent exercise (100% maximal aerobic speed, consisted of 1-min repetitions at MAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…This is consistent with an adult study showing an increase in HR but no change in during the recovery intervals of HIIE in male and female middle distance runners (Tocco et al., 2015). Interestingly, we also found that boys exhibited a lower % compared to girls during recovery intervals which is similar to a study on adults employing a HIIE protocol incorporating 60 × 8‐s intervals interspersed by 12‐s of passive recovery (Panissa et al., 2016). This sex difference may be explained by the higher aerobic fitness of boys since higher aerobic fitness is associated with a faster recovery of during the recovery intervals of HIIE (Panissa et al., 2014).…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with an adult study showing an increase in HR but no change in during the recovery intervals of HIIE in male and female middle distance runners (Tocco et al., 2015). Interestingly, we also found that boys exhibited a lower % compared to girls during recovery intervals which is similar to a study on adults employing a HIIE protocol incorporating 60 × 8‐s intervals interspersed by 12‐s of passive recovery (Panissa et al., 2016). This sex difference may be explained by the higher aerobic fitness of boys since higher aerobic fitness is associated with a faster recovery of during the recovery intervals of HIIE (Panissa et al., 2014).…”
Section: Discussionsupporting
confidence: 89%
“…However, when comparing the effect of different high-intensity training programs, Panissa et al (2016) analyzed the acute lipid profile responses mediated by two protocols of high-intensity intermittent training (all-out exercise and fixed high-intensity intermittent exercise). They concluded that both modes of exercise lead to no improvements in lipid metabolism.…”
Section: Influence Of Training Variables On Lipoproteins and Rctmentioning
confidence: 99%